Innovation-Investment Activity of Enterprises In the Digital Economy - Erkin Khodjaev; Zebuniso Kuylanova (International Journal on Orange Technologies, 2023)
The article deals with the enterprise innovation-investment activity performance problem. In terms of markets high competitiveness it’s vital to get competitive advantages. Due to the scarce of financial resources and important role of innovations in the enterprise effi ciency it’s necessary to develop the innovation-investment activity management mechanism.